Obesity, Type-II Diabetes and the Use of Food Labels: A Malaysian Perspective - Mumtaz Hussain ,; Shariza Sahudin, (Journal of Pharmacy and Nutrition Sciences, 2019)
Nutritional labelling of processed foods serve to implement consumer-driven food choices in an attempt to reduce the myriad of food and obesity-related chronic diseases, including type-2 diabetes and heart disease, prevalent in modern societies and posing a significant strain on healthcare resources. Many countries, including Malaysia, have moved towards both voluntary and mandatory regulations to policy such public-health interventions, requiring disclosure of nutritional information on food labels. [1-3], often with particular emphasis on sugar, salt and fat content. The introduction of these policies demonstrates the considerable medical and economic burden of obesity and chronic diseases such as type-2 diabetes on healthcare, and recognition among policymakers of the need for dietary intervention through patient education. Various obstacles exist in ensuring consumers use nutritional labelling, including clarity of information, consumer health orientation, literacy levels, motivational factors and health education levels. It is clear however that consumers and patients need to be better informed to effectively utilise nutritional information in order to make better food choices to address the burden of obesity and non-communicable diseases such as diabetes.